EFFECT OF USING SONG IN IMPROVING STUDENTS' VOCABULARY MASTERY: A STUDY OF FIRST GRADE STUDENTS OF JUNIOR HIGH SCHOOL 4 AIR HANGAT - Setiyadi, Ari (Langue (Journal of Language and Education), 2024)
This study aims to determine the significant effect of using songs to improve students' vocabulary. This research is a type of experimental research. The researcher used a pre-test and post-test between the experimental and control groups. The researcher gave the treatment of teaching vocabulary using songs in the experimental class and without songs in the control class. The participants in this study consisted of 52 students from class A and B. After conducting the pre-test, it was found that the students had problems improving their English vocabulary. Then, the learning results in the experimental class showed a significant increase in the use of songs to increase students' vocabulary. The findings in this study indicate that song can be used as a technique to teach students vocabulary.